Community vertical stratification drives temporal taxonomic and phylogenetic beta diversity in a mixed broadleaf-conifer forest - Chai, Pengtao; Xie, Jiajie; Yang, Lisheng; Zheng, Rong; Bian, Yuxuan; Fu, Jiaqin; Wang, Yunquan; Chen, Jianhua (Frontiers in Ecology and Evolution, 2023)
Temporal change of beta diversity provides a better understanding of the extent and consequences of species composition in forest communities with the ongoing global climate change. However, relatively little is known about temporal beta diversity changes across vertical stratification in the forest. In this study, we divided more than 5,000 tree individuals from a mixed broadleaf-conifer forest into four vertical strata (i.e., shrub, subcanopy, lower canopy, and upper canopy) to quantify how vertical stratification drives the temporal change of taxonomic and phylogenetic beta diversity. We found that taxonomic beta diversity significantly decreased while phylogenetic beta diversity showed an insignificant increase after 5 years. When considering vertical stratification, taxonomic beta diversity in the subcanopy, lower canopy, and upper canopy significantly changed with inconsistent directions, but phylogenetic beta diversity in the shrub significantly increased. Moreover, the significant decrease in taxonomic beta diversity is mainly driven by changes in species composition in shrub and subcanopy stratification (with 85.89% contributions). The changes in phylogenetic beta diversity are driven by shifts in the shrub and upper canopy (with 96.02% contributions). Our study suggests that taking community vertical stratification into consideration contributes to a better understanding of temporal beta diversity in forest communities.